Meta-Analysis of the Effects of Sleep Duration, Exercise, and Family Income on Obesity in Children - Hanifah, Hanifah; Dewi, Arddha Maha Pawitra Dwi Puspita; Yuhanani, Arinda Mukti; Sastrawijayah, Jemmi; Murti, Bhisma; Munawaroh, Siti Mar’atul (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Obesity is still one of the problems in Indonesia. The obesity problem has grown into an epidemic, with more than 4 million people dying each year. Factors causing obesity such as lifestyle, lack of physical activity, poor diet habits, low family income, sleep duration, and others. This study aims to estimate the effect of sleep duration, exercise, and family income on obesity in children. Subjects and Method: A systematic review and meta-analysis were conducted using PRISMA guidelines and the PICO model. Population= children of 2-18 years. Intervention= short sleep duration, exercise, and high family income. Comparison= long sleep duration, no exercise, and low family income. Outcome= Obesity. Articles were collected from databases such as Google Scholar, PubMed, Science Direct, and ResearchGate. The literature search used the keywords “family income